Diary of a Wimpy kid The Getaway - Kinney, Jeff (London Puffin, 2017)
Diary of a Wimpy Kid : The Getaway (Book 12) (3Hbde (BJeff Kinney ... Greg Heffley and his family are getting out of town. It$1 (Bs freezing cold at home and his parents are stressed about Christmas, so they decide the whole family are going to escape to a tropical island! A few days in paradise SHOULD do wonders for Greg and his frazzled family. The trouble is this version of paradise turns out to include sun poisoning, stomach troubles and venomous creatures. Can their trip be saved, or will this island getaway end in disaster?s
English Stories
For children aged 11-15 years
Keywords: English stories